Implementasi Model Machine Learning dalam Mengklasifikasi Kualitas Air - Stacyana Jesika; Suci Ramadhani; Yohanna Permata Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Water quality is an important factor in maintaining human health and environmental sustainability. Water pollution is a major problem in Indonesia, so it is important to monitor and classify water quality effectively. Implementation of machine learning models in classifying water quality can provide important benefits in the environmental and health fields. This research uses two machine learning algorithms, namely KNN and SVM, to classify water quality. The water quality data used comes from the website www.kaggle.com, which was uploaded by MsSmartyPants in 2021 with the title